ANALISIS PSIKOLOGI TOKOH UTAMA DALAM ANIMASI “KOKORO GA SAKEBITAGATTERUNDA 心が叫びたがってるんだ “ KARYA MARI OKADA - Ni Putu Pradnyasumita Nakami Ayu; Wayan Nurita; Ni Wayan Meidariani (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2022)
This article discusses and aims to determine the personality of the main character Jun Naruse from the Animated Film Kokoro Ga Sakebitagatterunda by Mari Okada. This research was studied using descriptive qualitative method. The theory used is Sigmund Freud's subconscious theory and also the 7 classifications of emotions according to Krech which consist of the concept of guilt, pent-up guilt punishing oneself, shame, sadness and hatred. The data source in this study is the dialogue in the animated film Kokoro ga Sakebitagatterunda. This research uses the listening method and continues with the note-taking technique. The results of this analysis, found 9 data where two data are conscious and unconscious, and also 7 emotional classifications of Jun Naruse character. After analyzing 10 data, 9 out of 10 data have been obtained so that the researcher concludes that this Jun Naruse character is a mentally depressed person.